2013
DOI: 10.1126/science.1234654
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila H1 Regulates the Genetic Activity of Heterochromatin by Recruitment of Su(var)3-9

Abstract: Eukaryotic genomes harbor transposable elements and other repetitive sequences that must be silenced. Small RNA interference pathways play a major role in their repression. Here, we reveal another mechanism for silencing these sequences in Drosophila. Depleting the linker histone H1 in vivo leads to strong activation of these elements. H1-mediated silencing occurs in combination with the heterochromatin-specific histone H3 lysine 9 methyltransferase Su(var)3-9. H1 physically interacts with Su(var)3-9 and recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 34 publications
9
110
3
1
Order By: Relevance
“…Our previous findings showed that H1 is essential for fly development beyond the late larval stage and that it is required for normal chromosome architecture (19). Moreover, we found that H1 plays a particularly prominent role in the structure and genetic activity of heterochromatin, where it participates in epigenetic marking and transcriptional silencing of transposable elements through its interaction with the Su(var)3-9 methyltransferase and STAT92E (7,19,42). By generating transgenic fly lines expressing full-length H1 and six different mutant H1 polypeptides, we interrogated its structural domains for their roles in multiple H1-mediated processes in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous findings showed that H1 is essential for fly development beyond the late larval stage and that it is required for normal chromosome architecture (19). Moreover, we found that H1 plays a particularly prominent role in the structure and genetic activity of heterochromatin, where it participates in epigenetic marking and transcriptional silencing of transposable elements through its interaction with the Su(var)3-9 methyltransferase and STAT92E (7,19,42). By generating transgenic fly lines expressing full-length H1 and six different mutant H1 polypeptides, we interrogated its structural domains for their roles in multiple H1-mediated processes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of these sequences needs to be silenced for genome integrity. We described previously a role for Drosophila H1 in transcriptional repression of these sequences (7). We found that Drosophila H1 and the heterochromatin-specific histone methyltransferase Su(var)3-9 interact and cooperate to mark heterochromatin with H3K9me2, resulting in silencing of the repetitive elements.…”
Section: The C-terminal Domain Of H1 Is Involved In Silencing Transpomentioning
confidence: 99%
See 3 more Smart Citations